2022
DOI: 10.3332/ecancer.2022.1354
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the main barriers for participation in a population-based colorectal cancer screening programme in East Azerbaijan, Iran

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer and the second leading cause of death worldwide. However, CRC is considered as one of the most preventable cancers by which the mortality rates reduce about 60% through implementing the screening programmes. The present study aimed to evaluate the main barriers of CRC screening in a defined population. Method:Healthy individuals from all regions of the state were invited to participate in different healthcare centres. They were assessed by a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…It has proven difficult to reduce inequalities between socioeconomic subgroups as most interventions targeted at the entire population, are less efficient in the less privileged subgroups [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Previous research have identified barriers to screening participation such as perceived risk of disease, fear of the result, the faecal collection, expected discomfort, and invasiveness of the procedures [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These barriers are very unlikely to be of equal relevance to all individuals.…”
Section: Introductionmentioning
confidence: 99%
“…It has proven difficult to reduce inequalities between socioeconomic subgroups as most interventions targeted at the entire population, are less efficient in the less privileged subgroups [ [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Previous research have identified barriers to screening participation such as perceived risk of disease, fear of the result, the faecal collection, expected discomfort, and invasiveness of the procedures [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These barriers are very unlikely to be of equal relevance to all individuals.…”
Section: Introductionmentioning
confidence: 99%